Gaya Kepemimpinan, Lingkungan Kerja Terhadap Kinerja Pegawai Dan Motivasi Kerja Sebagai Variabel Intervening Di Upt Daerah Perhubungan Laut: Gaya Kepemimpinan, Lingkungan Kerja Terhadap Kinerja Pegawai Dan Motivasi Kerja Sebagai Variabel Intervening - Aprianto, Risano Rian; Ariadi, Wa; Meliala, Janita S (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Leadership style, work environment on employee performance and work motivation are always hot topics discussed in all academic circles. Leadership style is always associated with the behavior or attitude of a leader influencing his subordinates, motivating them so that they can work better. The study aims to determine and analyze the leadership style and work environment that directly or indirectly influence through work motivation on employee performance at the Merauke Sea Transportation Regional Upt. This study used a sample of 127 people. The analysis tool used is Smath PLS. The results of this study indicate that the direct influence of leadership style (GKp) on employee performance (KP) is positive and significant with a probability level (P-Value) of 0.001. For the direct influence of the work environment variable (LK) on employee performance (KP) has a probability (p-Value) of 0.019, meaning that the p-value is smaller than the alpha level of 0.05, so it can be said that the work environment (LK) has a significant effect on employee performance (KP). The work motivation variable (MK) on employee performance (KP) shows that it has a negative and insignificant effect on employee performance (KP). The leadership style variable (GKp) on work motivation (MK) shows that it has a negative and significant effect on work motivation (MK). The work environment variable (LK) on work motivation (MK) shows a positive and significant effect. The results of the indirect influence analysis show that work motivation cannot emphasize or strengthen leadership style and work environment on employee performance.